2009
DOI: 10.1080/15376510802455354
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase inhibition and nitric oxide are involved in muscle weakness that occurs in acute exposure of rats to monocrotophos

Abstract: Organophosphate poisoning in the context of self-harm is a common medical emergency in Asia. Prolonged muscle weakness is an important but poorly understood cause of morbidity and mortality of the poisoning. This study examined mitochondrial function and its modulation by nitric oxide in muscle weakness of rats exposed to an acute, oral (0.8LD50) dose of monocrotophos. Muscle mitochondrial ATP synthase activity was inhibited in the rat in acute exposure to monocrotophos while respiration per se was not affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…[140][141][142] Depression of NADH cytochrome c reductase, succinate cytochrome c reductase, and CcOX activity in the mitochondrial respiratory chain, reduction of mitochondrial transmembrane potential and ATP concentration, elevation of ADP/ATP ratio, induction of LDH release, and necrotic cell death occurred following OP poisoning. [143][144][145][146] Moreover, this pesticide induced cholinergic receptor-independent necrotic cell death. Reduction of SDH and elevation of LDH suggest that anaerobic metabolism was favored while aerobic oxidation of pyruvate was impaired after OP exposure.…”
Section: Musclementioning
confidence: 99%
“…[140][141][142] Depression of NADH cytochrome c reductase, succinate cytochrome c reductase, and CcOX activity in the mitochondrial respiratory chain, reduction of mitochondrial transmembrane potential and ATP concentration, elevation of ADP/ATP ratio, induction of LDH release, and necrotic cell death occurred following OP poisoning. [143][144][145][146] Moreover, this pesticide induced cholinergic receptor-independent necrotic cell death. Reduction of SDH and elevation of LDH suggest that anaerobic metabolism was favored while aerobic oxidation of pyruvate was impaired after OP exposure.…”
Section: Musclementioning
confidence: 99%
“…Since, there are limited data about the hepatotoxicity of OPs in humans, it is not certain whether changes in biochemical parameters indicate actual liver damage. (90)(91)(92)(93)(94), energy production (93,(95)(96)(97), and cell death (98)(99)(100). Several studies have found an association between mitochondrial dynamics and malathion-induced drop in mitochondrial ATP synthesis in rat liver (9) or quinalphos and acephate effects on liver succinic dehydrogenase (84,85,101) and ATPase activities (87) -all of them the key enzymes for oxidative phosphorylation.…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
“…32 Increased level of NO is a natural sequence to the inhibition of AChE by OPs. 9 The results showed that there is a significant increase in nitrate (measured as nitrite) in plasma and lung in MP-treated group. Therefore, we make a conclusion that the change of NO level is harmful to lung tissue.…”
Section: Discussionmentioning
confidence: 94%